2023
DOI: 10.3390/nu15092161
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acids Metabolism and Their Roles in Retinopathy: From Relevance to Mechanism

Abstract: Retinopathy is one of the leading causes of irreversible blindness and vision loss worldwide. Imbalanced nutrients play important roles in the pathogenesis and pathophysiology of retinal diseases. Branched-Chain Amino Acids (BCAAs), as essential amino acids, perform a variety of biological functions, including protein synthesis, glucose metabolism, lipid metabolism, inflammation, and oxidative stress in metabolic tissues of diabetes and aging-related diseases. Recently, it has been shown that BCAAs are highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…We found causal relationships between seven metabolites in the amino acid metabolic pathway and DR. Amino acids participate in energy metabolism and regulate various metabolic pathways through gluconeogenesis ( 30 ). Previous studies have highlighted the significant role of amino acids in DR ( 30 32 ). Our findings specifically focused on the roles of tryptophan (TRP) and kynurenines (KYN) in DR. TRP serves as a primary origin for a range of bioactive molecules, including KYN, 5-hydroxytryptamine, melatonin, niacin and indoles ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found causal relationships between seven metabolites in the amino acid metabolic pathway and DR. Amino acids participate in energy metabolism and regulate various metabolic pathways through gluconeogenesis ( 30 ). Previous studies have highlighted the significant role of amino acids in DR ( 30 32 ). Our findings specifically focused on the roles of tryptophan (TRP) and kynurenines (KYN) in DR. TRP serves as a primary origin for a range of bioactive molecules, including KYN, 5-hydroxytryptamine, melatonin, niacin and indoles ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of microglia is stimulated by extracellular signals, among which glucose and its derivative metabolites figure prominently [45][46][47][48]. Chronic hyperglycemia activates complex pathophysiologic processes in DR, comprising ischemia, hypoxia, dyslipidemia, and advanced glycation end products (AGEs).…”
Section: The Activation and Polarization Of Microglia In Drmentioning
confidence: 99%
“…In recent years, the emerging literature on immunometabolism is defining new roles for cellular metabolic pathways in microglia polarization in DR [25,45,46,48,63]. Immunometabolism indicates the metabolic processes within immune cells, thereby influencing the destiny and functional outcomes of these cellular entities [64][65][66].…”
Section: The Immunometabolism Of Microglia In Drmentioning
confidence: 99%
“…Catabolism of BCAAs provides nitrogen for the synthesis of glutamate, and glutamate plays an important role in DR neurodegeneration as it is the major excitatory neurotransmitter in the CNS and retina. Branched chain amino acids (BCAAs) are associated with glutamate toxicity contributing to retinopathy (160), especially in DR and AMD. It has been found that BCAA supplements play a neuroprotective role by enhancing retinal ganglion cell survival, in addition to inflammatory and oxidative stress protective effects (160).…”
Section: Other Metabolitesmentioning
confidence: 99%
“…Branched chain amino acids (BCAAs) are associated with glutamate toxicity contributing to retinopathy (160), especially in DR and AMD. It has been found that BCAA supplements play a neuroprotective role by enhancing retinal ganglion cell survival, in addition to inflammatory and oxidative stress protective effects (160). BCAAs from protein diets are absorbed by the intestine, thus any dysregulation in absorption through altered gut microbiomes or intestinal malabsorption syndromes could be implicated in lower BCAA levels and susceptibility to retinopathy.…”
Section: Other Metabolitesmentioning
confidence: 99%